Critical reflections on methodological challenge in arts and dementia evaluation and research - Gray, Karen; Chester Evans, Simon; Griffiths, Amanda; Schneider, Justine M. (SAGE, 2017)
Methodological rigour, or its absence, is often a focus of concern for the emerging field of evaluation and research around arts and dementia. However, this paper suggests that critical attention should also be paid to the way in which individual perceptions, hidden assumptions and underlying social and political structures influence methodological work in the field. Such attention will be particularly important for addressing methodological challenges relating to contextual variability, ethics, value judgement, and signification identified through a literature review on this topic. Understanding how, where and when evaluators and researchers experience such challenges may help to identify fruitful approaches for future evaluation. This paper is based upon a presentation on the subject given at the First International Research Conference on the Arts and Dementia: Theory, Methodology and Evidence on 9 March 2017.